Information and Communication Technologies in Tourism 2013 2013
DOI: 10.1007/978-3-642-36309-2_28
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Customer Role Learning During Self-Service Technology Encounters

Abstract: The advance of self-service technologies (SSTs) in the tourism industry has highlighted the role of the customer as co-producer during service encounters. Customer usage of SSTs requires that they have acquired the needed skills and knowledge towards operating the SST efficiently. Despite the recognition of the importance of customer role clarity and ability for successful SST encounters, there is a dearth of knowledge into the process of customer SST role learning. Therefore, this research contributes to know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However the evaluation of SST usage by customers at retail grocery store is important (Orel & Kara, 2014). Kelly, Lawlor, and Mulvey (2010) suggested that there is no substantial evidence of a widely accepted SST adoption model. The earliest literature was technology adoption model (TAM) by Davis (1989) and theory of reasoned action (TRA) by Kallweit, Spreer, and Toporowski (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However the evaluation of SST usage by customers at retail grocery store is important (Orel & Kara, 2014). Kelly, Lawlor, and Mulvey (2010) suggested that there is no substantial evidence of a widely accepted SST adoption model. The earliest literature was technology adoption model (TAM) by Davis (1989) and theory of reasoned action (TRA) by Kallweit, Spreer, and Toporowski (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technology has radically changed the business landscape (Gallaugher, 2010;Schön, 2017). Among the range of new technologies developed within the last several decades, self-service technology (SST), or -technological interfaces that enable customers to produce a service independent of direct service employee involvement‖ (Meuter et al, 2000, p. 50), has attracted a great deal of attention from marketing scholars and practitioners (Kelly et al, 2010). Notable examples include automated teller machines (ATMs), pay-at-the-pump machines, and telephone banking or, more recently, automated hotel and grocery store checkouts, airline check-in systems for e-ticket holders, in-store kiosks for product information, web-based purchasing, and Internet transactions (Orel & Kara, 2014;Yang & Klassen, 2008).…”
Section: Introductionmentioning
confidence: 99%